Respuesta :

Answer:

Let's put this function into slope-intercept form.

y = mx + b

where m is the slope

and b is the y-intercept

We know the y intercept is -3 since f(0) = -3

Thus, b = -3

To find the slope, use the equation m = (y1 - y2) / (x1 - x2)

x1 = 0

y1 = -3

x2 = 7

y2 = 11

Note: these values came from the given information

m = (-3 - 11) / (0 - 7)

= (-14) / (-7)

= 2

m = 2

Plug the values of m and b into y=mx + b

y = 2x - 3

That's your answer.

Step-by-step explanation:

ACCESS MORE